Applications of Radio Frequency Heating in Food Processing (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Radiofrequency (RF) heating has been identified as one potential thermal treatment method with which to replace chemical fumigation and other conventional thermal methods because it is relatively easy to apply and leaves no chemical residues. RF equipment is commercially available today and is commonly used by the baking industry for the final drying of crackers, as well as by other industries. It involves the direct transfer of electromagnetic energy into bulk materials, providing fast and volumetric heating. This Special Issue aims to focus on recent developments in and applications of RF heating in food processing, such as disinfestation, drying, pasteurization, sterilization, temping, and thawing. This Special Issue will provide major methods, research strategies, and protocols used in the development of environmentally friendly food processes based on RF energy.